PERSEPSI SISWA SMP 3 BATUSANGKAR TERHADAP FILM PENGKHIANATAN G-30S/PKI - Habibullah Habibullah; Marhen Marhen (KINEMA: Jurnal Komunikasi dan Penyiaran, 2023)
This study aims to determine the students' perception of SMP 3 Batusangkar on the film betrayal of G30S/PKI. The type of research that the author uses is descriptive qualitative research. The data collection technique that the author uses is through observation, documentation and interviews. The betrayal of G30S/PKI is a documentary type of film. The film G30S/PKI is very good for the general public to watch, because this film tells the history of Indonesia during the coup carried out by the PKI. But this film contains many violent scenes. Second: The value of the struggle in the G30S/PKI film is very meaningful and worthy of our example. In this film, we can see the struggle in overcoming the betrayal of the G30S/PKI. We as the younger generation must also know the history of Indonesia and there are many positive things that we should emulate from Indonesian heroes.